"It's Not the Asperger's That Causes the Anxiety, It's the Communication": Person-Centered Outcomes of Hope and Recovery in a Cultural–Clinical Borderland. Issue 2 (April 2018) - Walsh, Irene P.; Delmar, Patricia; Jagoe, Caroline
Abstract : This article focuses on a narrative account of a therapeutic journey experienced by 2 of the authors: an individual (P.D.) with a diagnosis in adulthood of autism spectrum disorder (ASD) and a speech–language pathologist/researcher (I.W.). Instead of adopting a traditional expert clinician treating an impaired patient stance in a highly formalized clinical setting, with concomitant role expectations of power and perceived inequality, a cultural–clinical borderland was coconstructed. The figurative notion of borderland in this context is used to describe a physical and psychological space characterized by a more flexible, informal, and authentically shared therapeutic relationship, influenced by a merging of cultures. The cultures at play in this context were an ASD and non-ASD culture and the culture and practice of speech–language pathology. Accounts of social communication experiences, challenges, and anxieties focused on personal reflections, when misunderstandings and miscommunications surfaced from perceived cultural differences. Instead of reinforcing experiences of otherness and difference—which may be an inadvertent by-product of impairment-focused therapy—a positive trajectory of hope and recovery emerged from these interactions when they were placed within a person-centered context.